The Politics of Prosecutorial Independence in Anti-Corruption Policy - Febridiansyah, Febridiansyah; Sugeng Riyanto; Rahimah Embong; Amir Firmansyah (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2025)
The independence of the Attorney General’s Office in Indonesia remains weak due to persistent political influence, as the Attorney General is appointed by the President. Despite reform initiatives since 2000, including the establishment of reform teams, these efforts have yet to create a professional and independent institution, particularly in the prosecution of corruption. This study analyzes the institutional position of the Prosecutor’s Office and propose new legal policy directions to enhance its independence in combating corruption. Using a normative legal method with statutory and comparative approaches, the research examines prosecutorial systems in various countries to identify best practices. The findings reveal that prosecutors' law permits executive intervention because of the absence of clear constitutional provisions defining the Attorney General’s Office. Its ambiguous status between the executive and judiciary weakens professionalism and accountability. Therefore, a constitutional amendment is necessary to establish the Prosecutor’s Office as an independent state institution, with explicit regulations on its authority, accountability, appointment and dismissal procedures, and qualifications and tenure of the Attorney General. Strengthening the Prosecutor’s role as dominus litis within an integrated justice system also requires enhancing transparency, public participation, reforming internal legal culture, and adopting international best practices.